Characterization of cassava production systems in Vietnam - Le, Dung Phuong; Labarta, Ricardo Antonio; Haan, Stef de; Maredia, Mywish K.; Becerra López Lavelle, Luis Augusto; Nhu, Lien Thi; Ovalle, Tatiana M.; Nguyen, Vu Anh; Pham, Nhan Thi; Nguyen, Hy Huu; Nguyen, Hien Trong; Le, Kha Quy; et al. (International Center for Tropical Agriculture, 2019)
Using a nationally representative survey of cassava-growing households in Vietnam and a robust method of varietal identification based on DNA fingerprinting, this paper provides a broad picture of cassava production and socio-economic characteristics of cassava producers in the country. It presents a descriptive analysis of cassava production practices, varietal use, varietal preferences, as well as cassava utilization, and marketing. Results indicate that more than 85% of the cassava area in Vietnam is planted to improved varieties. The average yield at national level is 19 tons per hectare. About 69% of total cassava produced per household is sold as either fresh roots and/or dried chips. The remaining 31% is either for own consumption or for livestock feed. Of all the six regions surveyed, the Southeast is characterized by the most intensive cassava production practices. It also has the largest average cassava area per household, the highest percentage of tractor use, and a higher percentage of fertilizer application on cassava fields.